3D-printed polylactide/hydroxyapatite/titania composite filaments - Olam, Mikail; Tosun, Nihat (Elsevier Science Sa, 2022)
In this study, polylactic acid (PLA) based polymer composite filaments containing titanium dioxide (titania, TiO2), synthetic hydroxyapatite (HA), and natural hydroxyapatite (NHA) have been developed for biomedical applications. By using these composite filaments fabricated, 3D prints were easily printed on the fused deposition modeling (FDM) printer. The chemical and physical properties of PLA/HA/NHA/TiO2 composite prints were investigated. According to the DSC/TGA analysis of the 3D printing samples, the maximum operating temperature of the composites formed in PLA/HA/NHA/TiO2 blends was approximately 300 degrees C. With the addition of 1% HA/4% TiO2 to PLA, the glass transition temperature was 71 degrees C and the melting temperature was 167 degrees C. According to FTIR analysis, HA/NHA/TiO2 additives did not cause a change in the chemical structure of PLA. According to SEM analysis, TiO2 caused raster gaps to decrease and HA caused raster lines to be smoother. In EDX and Mapping analysis, it was seen that HA/NHA/TiO2 was homogeneously distributed in PLA. Stirring the PLA/HA/NHA/TiO2 mixtures at 100 rpm for 12 h was sufficient for homogeneous distribution.
Keywords: Chemical analysis; Physical analysis; Polylactide; Hydroxyapatite; Titania